Blade of Coronis - Doner, Matthew Thomas (East Carolina University, 2026)
This thesis presents the first seven chapters of an original fantasy novel centered on Aster Nari, a newly inducted knight of the Order of the Knights of Coronis, a religious knighthood devoted to the patron god of death. The narrative follows Aster as he graduates from the Order’s academy and enters a world in which the ideals of his training begin to conflict with the realities of war and political power. The story is set in a fictional world where religious institutions, divine authority, and military governance intersect, shaping both the moral framework and lived experiences of those within them. Through Aster’s perspective, the novel explores themes of duty, mortality, faith, and personal identity in the face of institutional expectations. The narrative is written in close third-person perspective, allowing readers intimate access to Aster’s thoughts, perceptions, and emotional responses while maintaining the narrative flexibility of third-person storytelling. A distinctive stylistic element of the work is the integration of italicized internal reflections and journal excerpts from Aster himself. These passages serve two related functions. First, they provide immediate insight into Aster’s internal reactions to unfolding events, capturing moments of doubt, realization, or fear that occur alongside the story's external action. Second, the italicized journal entries create the framing implication that the narrative itself has been reconstructed from Aster’s personal writings after the fact. This structure allows the story to function both as a present-tense narrative experience and as a reflective record of events already lived, subtly blurring the boundary between memory, documentation, and storytelling. The central conflict of the opening chapters emerges from a contradiction within Aster’s identity as a knight of Coronis. The Order teaches that its knights must not fear death, as they serve the divine authority that governs the natural passage between life and the afterlife. Death, within their doctrine, is not an enemy but a necessary and sacred transition within the cosmic order. However, the Order’s independence has recently been compromised. Due to a failing war effort, the military forces of the nation of Mavron have purchased the patronage of the Knights of Coronis, effectively turning the religious knighthood into a military asset. As a result, newly graduated knights are now expected to serve in active wartime roles under the authority of Mavron’s generals. This political shift forces Aster to confront a personal contradiction. While the Order teaches him not to fear death, he finds himself deeply unsettled by the prospect of dying not in the service of divine purpose, but as a soldier in a national war. This tension raises a fundamental question within Aster’s mind: does he truly not fear death, as he has been trained to believe, or has he merely never faced a situation in which that belief was truly tested? The difference between dying as a sacred servant of a god and dying as a tool of a nation becomes a central psychological and philosophical dilemma for the character. Throughout the first seven chapters, Aster’s internal conflict unfolds alongside his transition from cadet to active knight. The narrative begins during the final hours before his graduation ceremony, introducing his relationships with fellow cadets and establishing the institutional culture of the Order’s academy. These early chapters focus on the emotional atmosphere surrounding graduation, the expectations placed upon the cadets, and the looming reality that their futures will soon be determined by external powers. As the ceremony proceeds, the cadets are assigned to divisions within Mavron’s military, revealing how the Order has been absorbed into the broader machinery of war. Aster’s assignment places him in a specialized military division, separating him from several of the companions he trained with. This moment marks the beginning of his departure from the structured certainty of the academy and into a world where the ideals of knighthood must contend with the ambiguity and brutality of wartime service. The journal entries interspersed throughout the narrative further complicate the reader’s understanding of Aster’s mindset, offering reflections that suggest both introspection and hindsight. In doing so, they reinforce the idea that the story is not only about the events themselves, but also about how those events are remembered and interpreted by the individual who experienced them. Ultimately, the opening portion of the novel establishes the thematic foundation for a larger narrative exploring the relationship between faith, mortality, and institutional loyalty. By placing a character trained to accept death into a situation where the meaning of that death becomes uncertain, the story examines how belief systems are tested when confronted with political realities. Through its combination of close third-person narration, reflective journal fragments, and character-driven conflict, the work explores the psychological complexity of a knight whose greatest struggle lies not in battle but in reconciling the ideals he was taught with the world he must now serve.
Keywords: Creative Writing